2016
DOI: 10.7554/elife.17688
|View full text |Cite
|
Sign up to set email alerts
|

The influence of evidence volatility on choice, reaction time and confidence in a perceptual decision

Abstract: Many decisions are thought to arise via the accumulation of noisy evidence to a threshold or bound. In perception, the mechanism explains the effect of stimulus strength, characterized by signal-to-noise ratio, on decision speed, accuracy and confidence. It also makes intriguing predictions about the noise itself. An increase in noise should lead to faster decisions, reduced accuracy and, paradoxically, higher confidence. To test these predictions, we introduce a novel sensory manipulation that mimics the addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
153
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 130 publications
(176 citation statements)
references
References 66 publications
21
153
1
1
Order By: Relevance
“…In contrast, the aware model predicts a downward shift, with predicted ‘% more visible’ at d′ = 0 of 42.7%, which is significantly smaller than the ‘% more visible’ at d′ = 0 shown by subjects (t(13) = 3.629, p = .003) (Figure 2b). Thus, the blind model correctly predicted visibility would increase as a result of TMS in keeping with other findings in the literature (Rahnev et al 2011; Rahnev, Bahdo, et al 2012; Fetsch et al 2014; Zylberberg, Roelfsema, and Sigman 2014; Rahnev, Maniscalco, et al 2012; Zylberberg et al 2016), but the aware model incorrectly predicted visibility would decrease in concert with the reduction in objective performance. The aware model’s incorrect interpretation is in line with the hypothesis that TMS simply produces near-threshold conscious perception by reducing introspective reports in concert with a reduction in objective performance (e.g., Lloyd et al, (2013)).…”
Section: Resultssupporting
confidence: 86%
See 3 more Smart Citations
“…In contrast, the aware model predicts a downward shift, with predicted ‘% more visible’ at d′ = 0 of 42.7%, which is significantly smaller than the ‘% more visible’ at d′ = 0 shown by subjects (t(13) = 3.629, p = .003) (Figure 2b). Thus, the blind model correctly predicted visibility would increase as a result of TMS in keeping with other findings in the literature (Rahnev et al 2011; Rahnev, Bahdo, et al 2012; Fetsch et al 2014; Zylberberg, Roelfsema, and Sigman 2014; Rahnev, Maniscalco, et al 2012; Zylberberg et al 2016), but the aware model incorrectly predicted visibility would decrease in concert with the reduction in objective performance. The aware model’s incorrect interpretation is in line with the hypothesis that TMS simply produces near-threshold conscious perception by reducing introspective reports in concert with a reduction in objective performance (e.g., Lloyd et al, (2013)).…”
Section: Resultssupporting
confidence: 86%
“…Alternatively, it may be possible for an observer to be unaware of noise or other changes in its sensory processing system (Ko and Lau 2012; Zylberberg et al 2016; Zylberberg, Roelfsema, and Sigman 2014), as has also been suggested in cases of sensory adaptation (Seriès, Stocker, and Simoncelli 2009). In the current paradigm, such an observer would be metacognitively blind , i.e.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Relaxing some of H and M’s assumptions (e.g. including noise that scales with the strength of the evidence [Zylberberg et al, 2016]) caused even stronger crosstalk.
10.7554/eLife.17331.003Figure 1.Interaction between the accuracies at L1 and L2.We computed the psychometric function for the L2 decision for trials with a correct (green traces) or erroneous (red) decision at L1. Left, H and M model with infinite bounds collapsing after 500 ms. Middle, H and M model with high bounds that are stable.
…”
Section: Introductionmentioning
confidence: 99%